Investigating the time‐lapsed effects of rigid cervical collars on the dimensions of the internal jugular vein. Issue 2 (26th October 2018) - Kroeker, Jenna; Keith, Jay; Carruthers, Hailey; Hanna, Cherry; Qureshi, Natasha; Calic, Masa; Kaye, Meagan; Solow, Marissa; Coey, James; Sulaiman, Sara
Abstract : Protocol advocates the use of rigid cervical collars (RCCs) in head trauma patients as they are at risk of concomitant cervical spine injury. Literature has shown RCCs to be a potential cause of venous outflow obstruction, changing internal jugular vein (IJV) cross‐sectional area (CSA), and raising intracranial pressure (ICP). This study aims to investigate the effects of applying a RCC, for a period of four hours, on the dimensions of the IJV, in healthy participants. Seventeen participants (nine male, eight female) took part in this study. Circumference and CSAs of the IJV were measured bilaterally by a single observer using a GE LOGIQ e ultrasound system. Measurements were taken pre‐RCC application, immediately after, every hour over four hours, and five minutes postcollar removal. The CSA of the IJV was 8.3 ±6.0 mm 2 pre‐RCC application. The CSA of the IJV doubled (18.92 ±10.55 mm 2 ) after four hours and decreased back to 9.36 ±6.8 mm 2 five minutes postcollar removal. The circumference of the IJV was 17.29 ±6.03 mm pre‐RCC application, increasing to 20.34 ±5.59 mm by the end of the fourth hour and returning to 16.14 ±5.16 mm five minutes postcollar removal. Related‐samples Friedman's ANOVA test showed statistically significant differences for both left and right CSAs and circumferences of the IJV measured across the four hours ( P ‐value<0.05). Ultrasound assessment of CSA of the IJV may correlate with changes in ICP. Further studies may provide insight into the effects of collar design, and guide future trauma protocol to minimize intracranial pressure fluctuations. Clin. Anat. 32:196–200, 2019. © 2018 Wiley Periodicals, Inc.